The Dichotomy of Ekāyana in the Satipaṭṭhānasutta: Inclusive or Exclusive Meaning - Irawan, Dedy (LPPM STIAB JINARAKKHITA LAMPUNG, 2024)
This paper presents the ambiguity of the term ekāyana in the Satipaṭṭhānasutta in the light of inclusivism and exclusivism perspectives. Ekāyana is a familiar term in Buddhist Studies and Satipaṭṭhānasutta is a well well-known text in the Theravada insight meditation cycle. Ekāyana can be rendered in various ways according to the subjectivity and interpretation of each translator; thus, the term is ambiguous. This paper highlights the problem of Buddhist translation studies through analytical studies on several translations of the term. According to comparative analytical studies on different translations of ekāyana in the Satipaṭṭhānasutta, the researcher finds that interpretivism in translation is inevitable because finding the real meaning of a Buddhist term is an impossible task. Understandably, a translator of Buddhist texts imposes his interpretations when translating from ancient times until the present.